Diversification of α-ketoamides: Via transamidation reactions with alkyl and benzyl amines at room temperature - Singh S.; Popuri S.; Junaid Q.M.; Sabiah S.; Kandasamy J. (My University, 2025)
A wide range of N-tosyl α-ketoamides underwent transamidation with various alkyl amines in the absence of a catalyst, base, or additive. On the other hand, transamidation in N-Boc α-ketoamides was achieved in the presence of Cs2CO3. The reactions proceeded at room temperature and provided good to excellent yields of transamidation products under the optimized conditions. Broad substrate scope, functional group tolerance and quick conversions are the important features of the developed methodology. © The Royal Society of Chemistry.